Microbial and immune faecal determinants in infants hospitalized with COVID-19 reflect bifidobacterial dysbiosis and immature intestinal immunity - Gutiérrez- Díaz, Isabel; Sanz-Martínez, Miriam; Castro, Ana Mª; Velasco Rodríguez‐Belvís, Marta; Carreira, Nathalie; Jiménez, Santiago; Mangas, Carmen; Queralt, Macarena; Herrador, Marta; Martin‐Masot, Rafael; Ferrer, Pablo; Navas-López, Víctor Manuel; et al. (Springer, 2023)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread rapidly worldwide, seriously endangering human health. Although SARS-CoV-2 had a lower impact on paediatric population, children with COVID-19 have been reported as suffering from gastrointestinal (GI) symptoms at a higher rate than adults. The aim of this work was to evaluate faeces as a source of potential biomarkers of severity in the paediatric population, with an emphasis on intestinal microbiota and faecal immune mediators, trying to identify possible dysbiosis and immune intestinal dysfunction associated with the risk of hospitalization. This study involved 19 patients with COVID-19 under 24 months of age hospitalized during the pandemic at 6 different hospitals in Spain, and it included a comparable age-matched healthy control group (n = 18). Patients and controls were stratified according to their age in two groups: newborns or young infants (from 0 to 3 months old) and toddlers (infants from 6 to 24 months old). To characterize microbial intestinal communities, sequencing with Illumina technology of total 16S rDNA amplicons and internal transcribed spacer (ITS) amplicons of bifidobacteria were used. Faecal calprotectin (FC) and a range of human cytokines, chemokines, and growth factors were measured in faecal samples using ELISA and a multiplex system. Significant reduction in the abundance of sequences belonging to the phylum Actinobacteria was found in those infants with COVID-19, as well as in the Bifidobacteriaceae family. A different pattern of bifidobacteria was observed in patients, mainly represented by lower percentages of Bifidobacterium breve, as compared with controls. In the group of hospitalized young infants, FC was almost absent compared to age-matched healthy controls. A lower prevalence in faecal excretion of immune factors in these infected patients was also observed.
Keywords: COVID-19; Bifidobacteria; Faecal calprotectin; Faecal cytokines; Infant microbiota; Intestinal immaturity; Paediatric